The Basic concept of Economic Education At the Level of Supra Structure and Inrastruktur Politics in Indonesia - Refika, Refika; Hasibuan , Lias; Anwar Us , Kasful (International Journal of Educational Research & Social Sciences, 2021)
This article aims to get an overview of how basic concepts of economics ofeducation at the level of the supra-structure and infra-political structure inIndonesia. In that state of supra structure that includes the legislative, executive,judicial, and other state institutions, the government of Indonesia has made apolicy in writing that stated in the mandate of the constitution the Constitutionof 1945 of the State's obligation in financing education in Indonesia. Educationfunding is contained in Article 31 paragraph (4) of the 1945 Constitution thatthe State prioritize the education budget by 20% from APBN/APBD. If seen in astate of infra-structure that covers the center of the political power of thepeople, contained in elements of social organization, political figures,community leaders, the tools of political communication, and especially apolitical organization or political party is able to affect the workings of theapparatus of the public to express, distribute, translate, convert demands,support and the specific problems associated with the public interest, especiallyin this case the education sector, the government has given freedom inexpressing their opinions. It is proved that the Indonesian State has beenattempted in the give attention to education for its citizens. Because with aquality education will be able to improve economic growth and development ina Country. However, the education budget by 20% is considered not able tomaximize the improvement of the quality of education in Indonesia, so the needfor a new policy in increasing the percentage of the budget for education.